2022
DOI: 10.4314/gmj.v56i3s.14
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of knowledge and practice of newborn care among post-natal mothers attending immunisation clinics in Southeast Nigeria

Abstract: Objectives: Evidence-based newborn care practice recommended by WHO reduces neonatal mortality and improves neonatal outcomes. This study assessed the knowledge, practice-associated factors and predictors of essential newborn care among post-natal mothers in two primary health care centres in Southeast Nigeria.MethodsDesign: A cross-sectional total population studySetting: Two primary health care centres in two local government areas in Southeast Nigeria.Participants: Post-natal mothers who attended immunisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Hence, the importance of warranting central attention to this concept in pre- and postnatal care is underscored. These findings align with the notion that it is crucial to consider various factors, such as individuals’ and families’ characteristics, and contextual elements when providing care during the transition to parenthood [ 27 , 28 , 31 , 32 , 33 , 34 ]. As an example, the research conducted by Nomaguchi and Milkie [ 27 ] showed that parenting challenges and well-being are influenced by social, cultural, economic, and institutional factors.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…Hence, the importance of warranting central attention to this concept in pre- and postnatal care is underscored. These findings align with the notion that it is crucial to consider various factors, such as individuals’ and families’ characteristics, and contextual elements when providing care during the transition to parenthood [ 27 , 28 , 31 , 32 , 33 , 34 ]. As an example, the research conducted by Nomaguchi and Milkie [ 27 ] showed that parenting challenges and well-being are influenced by social, cultural, economic, and institutional factors.…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, working mothers and fathers with young children tend to experience less parenting stress compared to those who are not employed; however, this positive effect is influenced by the specific characteristics of one’s job [ 27 ]. Agu and colleagues’ study [ 31 ] identified being multiparous as a determinant factor for good practices. Moreover, their findings indicated that being married, older in age, residing in urban regions, and possessing a strong understanding of newborn care were additional predictors of positive practices.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations